2012
DOI: 10.1002/app.38451
|View full text |Cite
|
Sign up to set email alerts
|

Increasing solvent polarity and addition of salts promote β‐phase poly(vinylidene fluoride) formation

Abstract: This article investigates the effects of solvent polarity and salt addition on β‐phase poly(vinylidene fluoride) (PVDF) formation. Films were solvent cast in aprotic solvents of varying polarities with or without salt addition. Characterization was done by Fourier transformed infra‐red spectroscopy, differential scanning calorimetry, and scanning electron microscopy. Decreasing fractions of β‐phase PVDF was observed with increasing drying temperature when less polar solvents were used. The most polar solvent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Pristine PVDF polymer shows a degree of crystallinity ~ 45%, but for the sample prepared with NaCl, the sample shows an around 33%. Low et al [43] showed that when small amounts of NaCl are added to the PVDF solution, the salt, combined with free radicals near the crystalline surface promotes an increase of sample crystallinity [43]. However, beyond a critical concentration, the excess of salt will interact with the PVDF on the crystallite surface and promotes atoms dislocation, resulting in a decrease of the crystallinity degree of the PVDF sample (figure 5b).…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…Pristine PVDF polymer shows a degree of crystallinity ~ 45%, but for the sample prepared with NaCl, the sample shows an around 33%. Low et al [43] showed that when small amounts of NaCl are added to the PVDF solution, the salt, combined with free radicals near the crystalline surface promotes an increase of sample crystallinity [43]. However, beyond a critical concentration, the excess of salt will interact with the PVDF on the crystallite surface and promotes atoms dislocation, resulting in a decrease of the crystallinity degree of the PVDF sample (figure 5b).…”
Section: Thermal Characterizationmentioning
confidence: 99%
“…Many parameters could account for the lower dielectric constant values obtained for our samples. First, the content of the β-phase in our neat PVDF could be lower than that of the PVDF these authors used [7]. Increase in the β-polymorph, with all-trans chain conformation, in PVDF would make it more polarizable when the electric field is applied, as this phase is known to be piezoelectrically active [12,40].…”
Section: Broadband Dielectric Analysismentioning
confidence: 99%
“…The electroactivity of PVDF therefore mostly depends on the β-phase content. There are different methods to increase the β-phase content, such as mechanical stretching, use of polar solvents to dissolve and re-crystallize PVDF, electrical poling, and addition of fillers [5][6][7][8]. An example is graphene oxide (GO), which increases the β-phase content via interaction of the polymer chain with the oxygen-rich groups on the surfaces of the GO layers [9,10], or cellulose, where the polymer interacts with the -OH groups [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…Additives were also used to increase the β‐phase content in the final product, and each filler has its own mechanism to do that, such as graphene oxide which improves the β‐phase content through interaction between the electron‐rich oxygenated groups and the fluorine atoms, or cellulose which improves the β‐phase content by interaction between the polar hydroxyl groups and the fluorine atoms in the PVDF molecule . When polar solvents are used during PVDF processing, it can also lead to the formation of a β‐phase …”
Section: Introductionmentioning
confidence: 99%